2022
DOI: 10.1021/acsomega.2c02546
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors of Productivity of Tight Conglomerate Reservoirs Based on Random Forest Algorithm

Abstract: The tight conglomerate reservoir of Baikouquan formation in the MA 131 well block in the Junggar basin abounds with petroleum reserves, yet the vertical wells in this reservoir have achieved a limited development effect. The tight conglomerate reservoirs have become an important target for exploration and exploitation. The high-efficiency development scheme of a small well spacing three-dimensional (3D) staggered well pattern has been determined by a series of field tests on well pattern and well spacing devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Their analysis revealed that when predicting the oil storage rate, the most crucial variables were associated with the size of the oilfield, including cumulative oil production, number of wells, oil production (OIP), and rock volume [151]. In a separate study, Yu et al [152] utilized the random forest (RF) machine-learning algorithm to explore the factors influencing the high and stable production of a single well within a specific well group in the Junggar Basin. Their findings indicated that reservoir quality and oil saturation are the primary controlling factors, establishing the fundamental basis for achieving high and stable oil production [153].…”
Section: Multivariate Importance Evaluation Methods For Enhancing Oil...mentioning
confidence: 99%
“…Their analysis revealed that when predicting the oil storage rate, the most crucial variables were associated with the size of the oilfield, including cumulative oil production, number of wells, oil production (OIP), and rock volume [151]. In a separate study, Yu et al [152] utilized the random forest (RF) machine-learning algorithm to explore the factors influencing the high and stable production of a single well within a specific well group in the Junggar Basin. Their findings indicated that reservoir quality and oil saturation are the primary controlling factors, establishing the fundamental basis for achieving high and stable oil production [153].…”
Section: Multivariate Importance Evaluation Methods For Enhancing Oil...mentioning
confidence: 99%
“…This consists of a very high potential area in the south of the Bengkalis graben; three locations of high potential areas located on the banks of the Kiri trough and close to the Aman and Balam grabens; two locations of medium potential category II located east and northwest of the Bengkalis graben; and a medium potential area category located east of the Bengkalis graben.The study was limited because no feature relationship was established. Yu et al (2022) analyzed factors of productivity of tight conglomerate reservoirs based on random forest algorithm. The study proposed an evaluation model of major productivity controlling factors of thetight conglomerate reservoir to provide a reference for oil recovery based on a randomforest…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In recent years, the development of conglomerate reservoirs using scientific and efficient engineering methods has become a hot topic due to the continuous discovery of large oil and gas resources. Conglomerate reservoirs exhibit stronger heterogeneity compared to conventional sandstone reservoirs because they are filled with gravels in the matrix. Additionally, due to the low initial permeability, most of these reservoirs have undergone hydraulic fracturing to enhance the stimulated reservoir volume (SRV). , It makes more oil and gas easy to flow into production wells and be produced. , However, during the following long-term waterflooding stage, injected water will flow along these fractures, and high-conductivity channels form in the reservoir after high-intensity water injection. , Thus, to further exploit the remaining oil of fractured conglomerate reservoirs in the Xinjiang Oilfield, it is urgent to apply efficient water management techniques to enhance water conformance and oil production.…”
Section: Introductionmentioning
confidence: 99%